Communication in the Administration of Justice – Some Thoughts Through the Perspective of Children - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
In the practice, communication competencies are typically not among the most important expected competencies in terms of the relevant areas of children’s rights. This is particularly true for institutions such as the (criminal) justice system. However, meeting with a judge, lawyer, child protection expert, or even a representative of the investigating authority can have a long-term impact on the child involved.The aim of this chapter is to provide an insight from the perspective of minors into the range of relevant soft skills that appear alongside hard skills (i.e. expertise in the narrow sense); although in the workdays of institutions these have not yet received the recognition they deserve based on their importance.In addition to communication, these skills include the ability to cooperate, solve problems, be creative, and have emotional intelligence; the 21st century justice and child welfare system, the professional knowledge alone is no longer enough.On the expectations related to the communication method of judiciary (as an institutional system) and to the communication skills of its members (e.g. judges) the following chapters report deeply.Keywords: soft-skills, communication competence, map of competences, professional knowledge, training of experts